Free vascularized tibial periosteal graft with monitoring skin island for limb reconstruction: Anatomical study and case report. Issue 3 (1st December 2015) - Diaz‐Gallardo, Paula; Knörr, Jorge; Vega‐Encina, I.; Corona, Pablo S.; Barrera‐Ochoa, Sergi; Rodriguez‐Baeza, Alfonso; Mascarenhas, Vasco V.; Soldado, Francisco
Abstract : Several types of vascularized periosteal flaps have recently been described for the treatment or prevention of complex non‐union in pediatric patients. Among them, a vascularized tibial periosteal graft (VTPG), supplied by the anterior tibial vessels (ATV), has been used successfully as a pedicled flap in a few patients. The purpose of the study is to describe the periosteal branches of the ATV, as well as the cutaneous and muscular branches by means of an anatomical study. In addition, to report on the use of VTPG as a free flap with a monitoring skin island in a clinical case. A mean of 6.5 periosteal branches (range 5–7) were found. In all cases we located a cutaneous perforator branching from one of the periosteal branches located at the midlevel of the leg. We performed a two‐stage reconstruction of a recalcitrant non‐union and residual shortening of the right tibia in a 17‐year‐old boy. After nonunion focus distraction, we used a massive bone allograft fixed with a nail and covered by a VTPG as a biological resource. Allograft consolidation was achieved 5.5 months after surgery. At eighteen months after surgery, no complications were observed and the patient had resumed all his daily activities, despite a residual 2‐cm limb‐length discrepancy. VTPG may be considered as a valuable surgical option for bone reconstruction in complex biological scenarios in the young population. © 2015 Wiley Periodicals, Inc. Microsurgery 37:248–251, 2017.